The Role of Islamic Religious Education Teachers in Shaping the Inclusive Character of Students - Pujianti, Etika; Nugraha, Hendika Adi (CV. Tripe Konsultan, 2024)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in shaping the inclusive character of students in secondary school environments. An inclusive character is considered important in fostering attitudes of mutual respect, tolerance, and the ability to coexist in the midst of diversity. This study employs a qualitative approach with a case study method. Data were collected through in-depth interviews with PAI teachers, observations of the learning process, and analysis of related documents, such as syllabi and lesson plans. The results show that PAI teachers play a strategic role in shaping the inclusive character of students through three main aspects: (1) the use of discussion-based learning methods that encourage students to understand others' perspectives; (2) the role model demonstrated by teachers in exhibiting inclusive attitudes both inside and outside the classroom; (3) the integration of values of tolerance and respect for differences in the teaching materials and learning activities; (4) the use of a holistic approach, teaching religious, social, and moral values simultaneously, successfully instilling a deeper understanding of the concept of inclusivity. In addition, the study found that the success of shaping students' inclusive character highly depends on the competence of the teacher, the support of the school environment, and the relevance of the learning approach to students' social context. By optimizing the role of PAI teachers, students can better understand the importance of peaceful coexistence in the midst of diversity. The study concludes that PAI teachers are key agents in building students' inclusive character, and continuous training and development of teacher competencies are needed to support this role.